(untitled) (PIONIR: JURNAL PENDIDIKAN, 2025)
The role of school supervisors is crucial in enhancing the quality of education; however, their effectiveness in the context of junior high schools in rural areas has yet to be extensively studied. This research aims to analyze the role of school supervisors in controlling teacher quality at SMAN 3 Sungai Penuh, focusing on six indicators: inspecting, advising, monitoring, coordinating, reporting, and performing leadership. Using a qualitative approach, data were collected through in-depth interviews with one school supervisor and two teachers. The results indicate that the supervisor has performed their role quite well, but some areas need improvement, such as contextualizing supervision, balancing monitoring efforts, and decisiveness in decision-making. Based on these findings, the research proposes a new model called "Integrative-Contextual School Supervision" (PSIK), which integrates various aspects of the supervisor’s role within a holistic and adaptive framework. This model offers a more comprehensive approach to school supervision, considering the complexities of contemporary educational contexts. Implementing PSIK can improve the effectiveness of school supervision, teacher quality, and, ultimately, the overall quality of education. This study paves the way for developing school supervision practices that are more responsive to the challenges of 21st-century education. Keywords: School Supervisor, Controlling, Teacher Quality